2020
DOI: 10.1016/j.jcv.2020.104371
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of corona virus disease 2019 (COVID-19): A systematic review and meta-analysis

Abstract: Background: Since being first reported in Wuhan, China, in December 8, 2019, the outbreak of the novel coronavirus, now known as COVID-19, has spread globally. Some case studies regarding the characteristics and outcome of patients with COVID-19 have been published recently. We conducted a meta-analysis to evaluate the risk factors of COVID-19. Methods: Medline, SinoMed, EMBASE, and Cochrane Library were searched for clinical and epidemiological studies on confirmed cases of COVID-19. Results: The incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
496
10
39

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(584 citation statements)
references
References 42 publications
39
496
10
39
Order By: Relevance
“…However, Zhang et al found no signi cant correlation between the rate of severe events and the stage of cancer. (13) In terms of life threatening complications, the rate of ARDS in our patients was higher than in the metaanalysis reported by Yong et al (15) We found that the mortality rate was signi cantly higher among the patients with active cancer who had undergone cytotoxic chemotherapy less than 14 days prior to being admitted due to COVID-19, in comparison with the patients who did not have an active cancer and were not on recent cytotoxic therapies. This nding is similar to the report by Zhang et al(13) However, Kuderer et al (14) found no signi cant difference between undergoing cytotoxic chemotherapy within 30 days prior to COVID-19 diagnosis and its consequential mortality rate.…”
Section: Discussioncontrasting
confidence: 64%
“…However, Zhang et al found no signi cant correlation between the rate of severe events and the stage of cancer. (13) In terms of life threatening complications, the rate of ARDS in our patients was higher than in the metaanalysis reported by Yong et al (15) We found that the mortality rate was signi cantly higher among the patients with active cancer who had undergone cytotoxic chemotherapy less than 14 days prior to being admitted due to COVID-19, in comparison with the patients who did not have an active cancer and were not on recent cytotoxic therapies. This nding is similar to the report by Zhang et al(13) However, Kuderer et al (14) found no signi cant difference between undergoing cytotoxic chemotherapy within 30 days prior to COVID-19 diagnosis and its consequential mortality rate.…”
Section: Discussioncontrasting
confidence: 64%
“…Gastrointestinal symptoms were also present with diarrhoea being the most common one. As compared to the other studies (33,34,37,43,44), fever and cough had similar WPP, however, dyspnoea was found to be more prevalent in older patients as compared to the younger ones. Similarly, though diarrhoea has been noted as the most common gastrointestinal symptom in other studies (33,43) too, it has comparatively higher WPP in older population.…”
Section: Discussionsupporting
confidence: 37%
“…A marginal difference was observed when the subgroup analysis was done for patients in China (15%) and outside China (11%), which was not statistically signi cant. The published meta-analysis on COVID-19 has reported its mortality ranging from 3.1-5.5% (32)(33)(34)37). Hence, the fatality rate in our study is signi cantly higher, re ecting the poor resilience of older patients to COVID-19.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…As of April 22, 2020, a total of 2,471,136 laboratory-confirmed cases were reported worldwide, with a mortality rate of 6.8% [4]. Previous studies have shown that comorbidities in patients with COVID-19 are associated with poor prognosis, including hypertension, diabetes, chronic obstructive pulmonary disease (COPD), cardiovascular disease, and cerebrovascular disease [5][6][7].…”
Section: Introductionmentioning
confidence: 99%